THE ADOPTION OF TECHNOLOGICAL FACTORS INNOVATION BY EDUCATED WOMEN IN MINANGKABAU EMBROIDERY HANDICRAFT BUSINESS (JURNAL ECONOMICA : Research of Economic And Economic Education, 2020)
Abstract consists of English Abstract. Abstract (times new romans 10 bold and italic) The abstract is written in English containing the main issues, research objectives, short methods (locations do not need to be extracted), short research results (findings) and brief conclusions. The abstract is written in one paragraph, 50 to 300 words. (Times New Roman 10, single space, and italics). JEL Clasification: For keywords must use a code that refers to the American Economic Association. [Font Times New Roman 10 single-spaced, and italicized] Keywords: Maximum of 5 keywords in English separated by commas. [Font Times New Roman 10 single-spaced, and italicized